Phase transitions in solid Kr–CH₄ solutions and rotational excitations in phase II - Bagatskii, M.I.; Mashchenko, D.A.; Dudkin, V.V. (Физика низких температур, 2007)
The heat capacity CP of solid Kr–n CH₄ solutions with the CH₄ concentrations n = 0.82, 0.86, 0.90 as well as solutions with n = 0.90, 0.95 doped with 0.002 O₂ impurity has been investigated under equilibrium vapor pressure over the interval 1–24 K. The (T,n)-phase diagram was refined and the region of two-phase states was determined for Kr–n CH₄ solid solutions. The contribution of the rotational subsystem, Crot, to the heat capacity of the solutions has been separated. Analysis of Crot(T) at T < 3 K made it possible to estimate the effective conversion times τ and the energy gaps E₁ and E₂ between the tunnel levels of the A-, T- and A-, E-nuclear-spin species of CH₄ molecules in the orientationally ordered subsystem, and to determine the effective energy gaps E₁ between the lowest levels of the A- and T- species. The relations τ(n) and E₁(n) stem from changes of the effective potential field caused as the replacement of CH₄ molecules by Kr atoms at sites of the ordered sublattices. The effective gaps EL between a group of tunnel levels of the ground-state libration state and the nearest group of excited levels of the libration state of the ordered CH₄ molecules in the solutions with n = 0.90 (EL = 52 K) and 0.95 (EL = 55 K) has been estimated.